Reliability and reproducibility of three-dimensional cephalometric landmarks using CBCT: a systematic review - Cinthia de Oliveira LISBOA; Daniele MASTERSON; Andréa Fonseca Jardim MOTTA; Alexandre Trindade MOTTA (University of São Paulo, 2015)
Objective : The aim of this study was to review the reliability and reproducibility of 3D-CBCT (cone beam computed tomography) cephalometric landmark identification. Methods : Electronic databases (Pubmed, Scopus, Web of Science) were searched for papers published from 1998 to October 2014. Specific strategies were developed for each database, with the guidance of a librarian. Two reviewers independently analyzed the titles and abstracts for inclusion. The articles that met the inclusion and exclusion criteria were selected for full-text reading, and the selected articles went through methodological quality evaluation. After the exclusion of repeated articles, the titles of the remaining ones were read and 1,328 of them were excluded. The abstracts of 173 articles were read, of which 43 were selected, read in full and submitted to the inclusion and exclusion criteria. Fourteen articles or studies with reliable methodology and reproducibility remained. The data were collected, organized into figures and analyzed for determination of the reliability and reproducibility of the three-dimensional cephalometric landmarks. Results : Overall, the landmarks on the median sagittal line and dental landmarks had the highest reliability, while the landmarks on the condyle, porion and the orbitale presented lower levels of reliability. Point S must be marked in the multiplanar views associated with visualization in 3D reconstruction. Further studies are necessary for evaluating soft tissue landmarks.